Implementation Augmented Reality On Banjarnegara Culture As A Learning Media Using Marker-Based Tracking - Ilham Fitriyanto, Pratama; Azrino Gustalika, Muhamad (Universitas Medan Area, 2025)
Local Content is a subject that introduces the local culture of a region. At SD Negeri 1 Paseh, Banjarnegara, the teaching of Local Content faces challenges due to the lack of interactive learning media and conventional teaching methods that rely heavily on textbooks. This makes learning less engaging, lowers students' interest, and affects their understanding of Banjarnegara's culture. Thus, this study aims to develop a learning application based on Augmented Reality using the marker-based tracking method, which utilizes 2D images as markers to display 3D visuals. This approach helps enhance students' understanding of Banjarnegara's local culture in Local Content learning. The functional testing of the MULOK application was conducted using Blackbox Testing, which successfully evaluated its functionality. Distance and angle testing showed that markers were detectable within a range of 5-200 cm and at optimal angles between 20 and 160 degrees. Response time testing revealed an input-to-output response time of 1-2 seconds. Pretest and posttest evaluations were also applied to measure the application's effectiveness and to determine the improvement in students' understanding. The results showed an average score increase of 83.53%, demonstrating that Augmented Reality-based learning is more effective compared to conventional methods. Students do not need to visit the locations where culinary and handicraft products are made directly to observe and learn about them. By simply using the Augmented Reality Mulok application, students can effectively study Banjarnegara culture as part of Mulok learning